The relationship between physical health and psychological well-being among oldest-old adults - Cho, Jinmyoung; Martin, Peter; Margrett, Jennifer; MacDonald, Maurice; Poon, Leonard W. (My University, 2011)
Structural equation modeling examined health influences on psychological well-being among 306 octogenarians and centenarians from the Georgia Centenarian Study. There were significant direct effects of subjective health on affect and significant indirect effects of objective health through subjective health on positive affect and negative affect. Subjective health mediated between objective health and psychological well-being. These results highlight the status and perceptions of health as a critical indicator for well-being in extreme old age.
Keywords: Psychological well-being; Oldest old adults; Physical health